A balance of economic modernization and intergovernmental tensions - Abellán López, María Ángeles (Cuadernos de Gobierno y Administración Pública, 2016)
This article contains an overview of the modernization of the regional administrations since its inception until present. We distinguish roughly four modernizing cycles: the first is mainly identified with the search for legitimacy and survival of the regional administrations. The second is inspired by the New Public Management (NPM) and the emergence of a post-burocratic paradigm that enables the development of new methodologies. The third is characterized by the primacy of e-administration and quality policies applied to public services. Finally, the last cycle poses antagonistic tendencies, according to the outbreak of the current economic crisis.